NUTRITIONAL STATUS AND BODY COMPOSITION IN PERITONEAL DIALYSIS PATIENTS: RELEVANCE OF BIOIMPEDANCEMETRY (BCM®) FOR LONGITUDINAL MONITORING - Nodimar, Céline; Moreau, Karine; Combe, Christian; Chauveau, Philippe (Kidney research and clinical practice, 2012)
The protein-energy wasting is common in patients with renal failure including patients on peritoneal dialysis (PD) and is closely linked to an increased risk of morbi- mortality. The purpose of this study was to evaluate the relevance of bioimpedance spectroscopy (BIS) to assess longitudinal body composition (BC) modifications in incident and prevalent peritoneal dialyzed patients. 49 patients (16 women - 33 men) between January and December 2010 were included in this longitudinal, prospective, multicentric study. 18 of them (all men) were prevalent patients. Clinical (height, weight), biological (albumin, prealbumin, nPCR) and BIS (BCM®, Fresenius Medical Care) were collected at baseline, and months 3, 6 and 9. BC parameters are expressed as lean tissue index (LTI kg/m² for fat free mass/ height squared) and fat tissue index index (FTI kg/m² for fat mass/ height squared). Comparisons of data over time were conducted in pairs between 0 and 9 months. At baseline, albumin (34.1±6.1 g/L), prealbumin (0.39±0.12 g/L) and nPCR (0.90±0.24 g/24h) met the nutritional recommendations for PD patients. Mean weight was 71.7±15.0 Kg. Mean LTI was 12.6±3.4 kg/m² and FTI was 12.3 ± 6.1 kg/m². 37% of our population had an LTI below the 10th percentile and 16% have an FTI above the 90th percentile. After 9 months, mean weight remained stable for the whole population. At month 9, no change in the biological parameters was detected. LTI decreased significantly for all patients (-0.668±0.2 kg/m²), with a concomitant increase of FTI (1.05±0.27 kg/m²). These changes were greater in patients over 65 years, and faster in incident dialyzed patients. These changes were not influenced by residual renal function nor by the glucose exposition. We confirm that PD is associated with changes in BC, whether for incident or prevalent patients. The BCM®, a simple, reproducible and inexpensive technique, could be proposed in the systematic nutritional monitoring of PD patients, in order to detect early modification of nutritional status in those patients and then to adapt clinical management.